News of Death In Jumlah Fi‘liyyah In Obituarial Rubric Of Al-Ahrām Newspaper December 2017 – March 2018 Edition: Semantic Analysis - Farhani, Nada (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This study discusses news of death in the jumlah fi‘liyyah in the obituary rubric of Al-Ahrām (SKA) newspaper with the euphemisms contained there in. This study aims to reveal the fi'l form used and the choice of words or euphemisms in obituaries jumlah fi‘liyyah numbers in the opening sentences of the SKA obituary rubric, December 2017 – March 2018 edition. The theory used in this research is semantic. The data of this research is in the form of obituaries in jumlah fi‘liyyah in the opening sentence of the SKA obituary rubric advertisement. The method used in providing data is the listening method, with basic tapping and orthographic note-taking techniques as advanced techniques. At the data analysis stage, the method used is the distribution method with basic techniques for natural elements and advanced courses in the form of dissipation techniques and replacement techniques. As for the data presentation stage, the informal presentation method is used. Based on research conducted on obituaries in jumlah fi‘liyyah in the opening sentence of the SKA obituary rubric advertisement, eight variations of obituaries used based on the fi'l were found. The eight obituaries in jumlah fi‘liyyah are divided into three categories of fi'l forms, namely fi'l mujarrad ma'lūm, fi'l mazīd ma'lūm, and fi'l mazīd majhūl. The eight fi'ls in these three forms are euphemisms to replace /māta/ in BA. Thus, it is known that the perspective of the Arab nation in symbolizing someone's death with the choice of subtle words in the form of certain fi'l and visible religious symbols through the terms used.